Comparative investigation of antitumoral effectiveness of Rho-kinase inhibitor Y-27632, pravastatin and atorvastatin in anaplastic thyroid cancer cell culture - Erdinc Nayir; Selver Cor; Zuhal Mert Altintas; Kansu Buyukafsar; Rukiye Nalan Tiftik; Alper Ata; Ali Arican (Journal of Oncological Sciences, 2017)
Anaplastic thyroid cancer is an aggressive malignancy with a poor prognosis. In metastatic cases instead of treatment alternatives including surgery, radiotherapy, and chemotherapeutic regimens, targeted treatments should be sought for. Statins are 3-hidroxy-3 methylglutaryl-coenzyme A (HMG-CoA) reductase inhibitors, and inhibit conversion of HMG-CoA into mevalonate. Inhibition of mevalonate pathway Ras prenylation, can also inhibit tumoral growth. Rho/Rho kinase pathway has an important role in tumoral proliferation, and metastasis in which activity of ROCK increases leading to tumoral invasion. Herein we investigated antitumoral effectiveness of two HMG-CoA reductase inhibitor statins namely pravastatin, and atorvastatin, and Rho-kinase inhibitor Y-27632 in anaplastic thyroid cancer cell cultures through suppression of cellular proliferation. Various concentrations of pravastatin (20, and 60 μM), and atorvastatin (10, and 30 μM), Y-27632 (10, and 30 μM), and their combinations including pravastatin -Y-27632 (20 μM + 10 μM; 60 μM + 30 μM), atorvastatin - Y-27632 (10 μM + 10 μM, and 30 μM + 30 μM) solutions were prepared. Anaplastic thyroid cancer cell culture media were treated with these more water-soluble drug solutions of pravastatin which induced lower dose-, and time-dependent decreases in cellular indices relative to more lipid-soluble atorvastatin which also markedly suppressed cellular proliferation. Y-27632 also decreased cell indices in a dose-, and time-dependent manner. Combination of Y-27632 with pravastatin, and atorvastatin did not demonstrate additive, synergic or antagonistic interactions. HMG-CoA reductase, and also Rho-kinase inhibitors are promising treatment alternatives of anaplastic thyroid cancers. Further in vivo, and clinical studies are needed on this issue.